THE INFLUENCE OF THE ROLE OF AGRICULTURAL EXTENSION OFFICERS ON THE KNOWLEDGE LEVEL OF ROBUSTA COFFEE FARMERS ABOUT FARM CARD PROGRAM IN JUMO DISTRICT TEMANGGUNG REGANCY - Ananda Aulia Rahman; Dyah Mardiningsih; Tutik Dalmiyatun (Tadulako University, 2018)
Farm card program is tool of redemption transaction and payment of subsidized fertilizer for farmers. This research aimed to know the role of agricultural extension officers as a communicator, motivator and facilitator on the knowledge level of robusta coffee farmers about farm card program in Jumo District Temanggung Regency, to know the knowledge level of robusta coffee farmers about farm card program and to analized the influence of the role of agricultural extension officers role on the knowledge level ofrobusta coffee farmers about farm card program in Jumo District Temanggung Regency. This research was carried out on November 2017 until Januari 2018 in Jumo District Temanggung Regency. Research method wassurvey. Data analized with descriptive analysis and linear multiple regression analysis. Results of the research showed that the role of extension officers as a communicator, motivator, facilitator were good. The knowledge level of robusta coffee farmers about farm card program were good. The role of extension officers as communicators did not affecton the knowledge level of robusta coffee farmers about the farm card program, where as the role as motivator and facilitator influenced on the knowledge level of robusta coffee farmers about farm card program. The role of agricultural extension officers as a communicator, motivator and facilitator simultaneously influence the knowledge level of robusta coffee farmers about farm card program in Jumo District Temanggung Regency.